Effect of Influencers on Consumer Purchase Intention - Gautam, Ujjwata; Shrestha, Aashreya; Basnet, Riya; Khadka, Kushal; Ghale, Pujan; Jadhav, Suhel (New Perspective: Journal of Business and Economics, 2023)
This study examines the effect of influencers on consumer purchase intention in the urban areas of Nepal, specifically the major cities of Kathmandu and Lalitpur. The sample size for this study is 100 respondents, determined using the rule of 1:4. Descriptive statistics, correlation, ANOVA, and multiple regression were used to analyze the data. The findings suggest that marketers do not have to choose different influencers according to gender or levels of education, but rather according to age group. Additionally, marketers should consider using influencer marketing and choose influencers based on their use of influencer marketing tools, credibility in their content, and their product target market. This study adds to the existing research on the impact of social media and influencer marketing on consumer behavior in Nepal.